Foxwoods Casino Resort: An unusual experiment in economic development - D'Hauteserre, A.-M. (Economic Geography, 1998)
The Foxwoods Casino Resort owned by the Mashantucket Pequots of Connecticut is the largest gambling casino in the Western world. The Pequots' Connecticut location enabled the tribe to open a casino, with accessibility to a large market and limited competition. The opening of Foxwoods is also the result of changes in relationships between Americans and Indians and shifts in American attitudes toward gambling. As attitudes and laws change, however, there is little chance that another Indian Foxwoods will be created here or elsewhere in the United States.
6 citations (Crossref) [2023-10-31]
Keywords: American Indian sovereignty; Connecticut; Gambling; Mashantucket Pequots; Pequots people; USA; Connecticut; casino; dept.egm; gambling; indigenous population; recreational activity

The emergence and development of geographic thought in new england - Martin, Geoffrey J (Economic Geography, 1998)
Some of the early settlers of New England brought with them the works and thought of European geographers, notably Ptolemy, Munster, Cluver, Carpenter, and Varenius. Beginning in the 1600s the work of British geographers Gordon and Salmon and Guthrie and Pinkerton was acknowledged, preceding that of Jedidiah Morse, “Father of American Geography.” Morse led the way for a large number of geography texts written by Americans, emphasizing North America and characterized by Varenius's special geography. Early collegiate developments in New England geography were led by Harvard and Yale universities, the College of Rhode Island (later renamed Brown University), and Dartmouth College. The 20 or so normal schools throughout New England, introduced in the middle 1800s, constituted a nursery for geographic education. Also noted are more recent college and university geography departments established throughout the region, including notably Clark University. The founding of societies and associations in New England also furthered the cause of geography.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-602-143-244-317 tex.type: [object Object]
Keywords: Geography; Harvard; History; Morse; USA; New England; Varenius; Yale; dept.egm; geographical thought; geography education; history of geography